Betulinic Acid as a Potent and Complex Antitumor Phytochemical: A Minireview - Gheorgheosu, Dorina; Duicu, Oana; Dehelean, Cristina; Soica, Codruta; Muntean, Danina (Anti-Cancer Agents in Medicinal Chemistry, 2014)
Betulinic acid (BA), a natural compound with a lupan skeleton, has been highly investigated in the past decade for a plethora of beneficial properties, including anti-cancer, anti-inflammatory, anti-angiogenic, immune-modulatory, and anti-HIV effects. In particular, BA has been reported to be effective in vitro against tumor cell lines of different origins, and also in vivo, in animal models of cancer. The best characterized mechanism of its antitumor effect consists of triggering apoptosis via the mitochondrial pathway. BA has also an anti-metastatic effect via the prevention of the epithelial-to-mesencymal transition in highly aggressive melanoma cells. Furthermore, in the same model, BA is able to counteract the pro-invasive potential of the pro-tumoral protein neutrophil gelatinaseassociated lipocalin. The present review addresses the current state of knowledge regarding the anti-tumor effects of betulinic acid, a potent chemotherapeutic agent.
Keywords: Angiogenesis